Pengaruh Kepemimpinan Transformasional Dan Komitmen Organisasi Terhadap Kinerja Pegawai Melalui Disiplin Kerja Sebagai Variabel Intervening (Studi Pada Dinas Pekerjaan Umum Dan Penataan Ruang Provinsi Banten) - Setiadi, Muhamad Teguh; Lutfi, Lutfi (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2021)
The purpose of this study was to examine and analyze the influencing factors of transformational leadership and organizational commitment on employee performance through work discipline as an intervening variable. This study uses a descriptive quantitative method with a causal approach. The object of this research is the Department of Public Works and Spatial Planning in the Bina Marga Sector of Banten Province using a sample of 115 respondents. Questionnaire answers were measured using an interval scale of 1 – 10. The data were analyzed using the SmartPLS version 3.29 software. The results of this study stated that: 1). Transformational leadership has a significant effect on employee performance, the acquisition of a coefficient of 11.7%, 2). Organizational commitment has a significant impact on employee performance, obtaining a coefficient of 22.5% 3). Transformational leadership has a significant effect on work discipline in the acquisition of a coefficient value of 24.5%, 4). Organizational commitment has a significant effect on work discipline with the acquisition of a coefficient of 45.3%, 5). Work discipline has a significant effect on employee performance, the acquisition of a coefficient of 64.5%. Work discipline can mediate between transformational leadership and organizational commitment to employee performance partially.